Technology and safety of marine systems - Pillay, Anand (Elsevier Science, 2003)
Traditionally society has regulated hazardous industries by detailed references to engineering codes, standards and hardware requirements. These days a risk-based approach is adopted. Risk analysis involves identifying hazards, categorizing the risks, and providing the necessary decision support to determine the necessary arrangements and measures to reach a "safe" yet economical operating level. When adopting such an approach the abundance of techniques available to express risk levels can often prove confusing and inadequate. This highly practical guide to safety and risk analysis.
Keywords: Ships -- Safety measures.; Ships -- Safety regulations.; Ships -- Inspection.; elektronické knihy; electronic books